GAMIFICATION, MOBILE LEARNING, AND MICROLEARNING IN VOCABULARY INSTRUCTION: THE MEDIATING EFFECT OF LEARNING MOTIVATION ON VOCABULARY MASTERY - Hanafi; Anita Fatimatul Laeli (SOSIOEDUKASI, 2026)
This research seeks to analyze the impact of three factors, namely Gamification Strategy, Mobile Assisted Language Learning (MALL), and Microlearning Content, on Vocabulary Mastery while using Learning Motivation as a mediator. A cross sectional survey was implemented in this study, which adopted a quantitative approach and an explanatory research framework. Purposive sampling was employed to select 150 students enrolled in English Language Education and English Literature programs at various Indonesian universities. Data collection occurred through a 5 point Likert scale based online questionnaire. The analysis of the data relied on SmartPLS software, specifically using the Partial Least Square Structural Equation Modeling (PLS SEM) method. The results demonstrate that Gamification Strategy has a positive and significant impact, affecting both Vocabulary Mastery and Learning Motivation. Microlearning Content also proved to have a positive and significant effect on Vocabulary Mastery and Learning Motivation. In contrast, MALL showed no significant effect on either Vocabulary Mastery or Learning Motivation. Furthermore, Learning Motivation proved to have a significant effect on Vocabulary Mastery. The mediation test results indicate that Learning Motivation was able to mediate the effect of Gamification Strategy and Microlearning Content on Vocabulary Mastery, but was unable to mediate the effect of MALL on Vocabulary Mastery. This study affirms that the integration of gamification and microlearning within a mobile-based learning ecosystem is more effective in enhancing vocabulary mastery than the use of mobile technology alone. The findings of this study provide theoretical and practical contributions to the development of more interactive, adaptive, and learning motivation-oriented digital technology-based vocabulary learning strategies for students.